Fruiting efficiency: an alternative trait to further rise wheat yield - Gustavo A. Slafer (2015)
Further improvements in wheat yields are critical, for which increases in grain number would be required. In the recent past, higher grain number was achieved through increased growth of the juvenile spikes before anthesis, due to the reduction in stem growth. As current cultivars have already an optimum height, alternatives must be identifi ed for further increasing grain number. One of them is increasing fruiting effi ciency (grains set per unit of spike dry weight at anthesis). Fruiting effi ciency is the fi nal outcome of the fate of fl oret development and differences in this trait within modern cultivars would be related to higher survival of fl oret primordia. Then there are two alternative physiological pathways to improve fruiting effi ciency by allowing a normal development of most vulnerable fl oret primordia: an increased allocation of assimilates for the developing fl orets before anthesis, or reduced demand of the fl orets for maintaining their normal development. Both alternatives may be possible, and it might be critical to recognize which of them is the actual cause of differences in fruiting effi ciency. When considering this trait in breeding we must be aware of potential trade- offs and therefore it must be avoided that increases in fruiting effi ciency be constitutively related to decreases in either spike dry weight at anthesis or grain weight. In this review we described fruiting effi ciency and its physiological bases, analyzing genetic variation and considering potential drawbacks that must be taken into account to avoid increases in fruiting effi ciency being compensated by other traits